Evaluating fatigue behavior of asphalt binders and mixes containing Date Seed Ash - Foroutan Mirhosseini, Ali; Kavussi, Amir; Jalal Kamali, Mohammad Hossain; Khabiri, Mohammad Mehdi; Hassani, Abolfazl (Journal of Civil Engineering and Management, 2017)
Fatigue is one of the most occurring distresses in asphalt pavements. Asphalt binder plays a critical role in fatigue behavior of asphalt mixes. Modelling and predicting fatigue behavior of binders will result in more fatigue resistant mixes. In this research, possibility of using Date Seed Ash alongside two commonly used additives (namely, a siliceous and a limestone) as bitumen modifier were investigated. Then, the influence of these additives on fatigue behavior of asphalt binders and mixes was investigated. Linear Amplitude Sweep (LAS) test was carried out and Viscoelastic Continuum Damage (VECD) parameter was determined. In addition, Indirect Tensile Fatigue Test (ITFT) was performed on mixes containing these additives. Correlation equations were developed to link fatigue behavior of binders to those of mixes. The results showed acceptable agreement between binders and mixes fatigue testing results. In addition, with predicted models it was able to obtain the asphalt binders contribution to mixes fatigue resistance. However, in the case of ash modified samples, no good correlation was observed between fatigue behavior of binders and that of mixes.